Analisis Sumber dan Penggunaan Modal Kerja Terhadap Peningkatan Profitabilitas Pada Koperasi Serba Usaha Lorosae Makassar - Mattarima Mattarima; Mardiana Ibrahim; Sry Surya Rucmana (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2021)
The cooperative must manage the amount of working capital in accordance with the requitments of its operations, taking into account the source and use of funds in the working capital. This study aims to determine and analyze the seources and uses of working capital relation with profitability at KSU Lorosae Makassar. This type of research is quantitative descriptive research that describes how the application of the management of the sources and uses of working capital KSU Lorosae Makassar. The focus of this study is to report the financial KSU Lorosae Makassar consisting of the balance sheet and the income statement during the period 2018-2020. Data analysis used is the analysis of the sources and uses of working capital and ratio analysis profitability. The results showed that the management of the sources and uses of working capital KSU Lorosae Makassar for 3 years has increased and is quite effective in generating profits.